The implementation of the Merdeka English Curriculum in the teaching and learning process at SMA N 7 Halmahera Selatan - S Syamsia; Sinta Saiful (Jurnal Langua, 2025)
This research aims to investigate the implementation of the English Merdeka Curriculum in the teaching and learning process and to identify the problems encountered by teachers during the implementation of the English Merdeka Curriculum in the teaching and learning process at SMA Negeri 7 Halmahera Selatan. In Indonesia, the government has introduced the Merdeka Curriculum as part of an educational transformation aimed at improving learning outcomes, fostering critical thinking, and enhancing student engagement. The implementation of the Merdeka English Curriculum introduces new teaching methods, learning assessments, and technological integration, which significantly impact the teaching and learning process in senior high schools. The subject of this research is an English teacher who teaches class X students at SMA Negeri 7 Halmahera Selatan. The researchers used several techniques to collect data for this study. The methods used are observation, interview, and documentation. The result of this research was the English Merdeka Curriculum at SMA Negeri 7 Halmahera Selatan has been implemented well, following national education standards and fostering a positive learning environment. However, challenges such as teacher adaptation, resource limitations, student readiness, and professional development need to be addressed to further improve the curriculum’s effectiveness.